Exploring the service profit chain in a Thai bank. Issue 2 (10th April 2017) - Benjarongrat, Pichate; Neal, Mark
Abstract : Purpose: The purpose of this paper is to explore the service profit chain (SPC) in a Thai bank, to identify which service features customers understand to be most important in their customer satisfaction and engagement. Through this it is intended to evaluate and refine the SPC model. Design/methodology/approach: The research involved two phases: a qualitative inductive process of interviews with bank customers to identify what they considered to be the most important aspects of service in their own customer satisfaction/engagement; second, a survey phase, which theoretically developed these aspects of service, and operationalized them as variables for testing in a refined SPC model. Findings: The key service features for customers in their satisfaction and engagement were found to be convenience, courtesy, competence and internal branding. All had positive relationships with customer satisfaction/customer engagement. Customer engagement/satisfaction were further found to correlate with customer retention and acquisition. Interestingly, whereas all four service variables correlated with customer engagement and satisfaction, two of the variables – courtesy and internal branding – had stronger relationships with customer engagement. Practical implications: The inductive modeling and refinement of the SPC approach can be employed in different companies and cultural contexts to identify which features of service are most important to customers in influencing their customer satisfaction/engagement. Originality/value: This is the first study to use/evaluate the SPC approach in the Thai banking context; the first to use inductive methods to identify relationships between service features and customer satisfaction/engagement; and the first to examine courtesy, competence, convenience and internal branding in a holistic model with customer satisfaction/engagement and customer retention/acquisition.